Code-Switching Practices in the Nile Delta: A Comparative Study of Linguistic Fluidity Among Gen Z and Gen X EFL Learners - Wesam Khairy Morsi (Journal of English Language Teaching and Linguistics, 2026)
This study investigates code-switching as a form of linguistic fluidity among Egyptian EFL learners, focusing on how language practices are shaped by proficiency level, socio-cultural background, and generational positioning. Drawing on a convergent mixed-methods design, the research combines survey data from 154 participants with semi-structured interviews conducted with speakers from Generation Z and Generation X. Rather than treating code-switching as a random or deficient practice, the study situates it within established sociolinguistic theories that view language choice as socially meaningful, ideologically loaded, and deeply connected to identity construction. The findings reveal that advanced learners, particularly younger urban speakers, tend to use code-switching as a strategic and expressive resource aligned with cosmopolitan identities and digital culture. In contrast, intermediate learners from rural or semi-rural backgrounds employ code-switching primarily as a functional scaffold to facilitate comprehension and communication. Generational differences further shape these patterns, with Generation Z embracing linguistic hybridity and translanguaging, while Generation X prioritizes linguistic restraint and cultural continuity. The study argues that code-switching among Egyptian EFL learners reflects broader social transformations related to globalization, mobility, and shifting notions of belonging. The paper concludes by discussing pedagogical and theoretical implications for sociolinguistics and EFL education in diglossic and postcolonial contexts.